UPAYA PEMANFAATAN GATHOT (SINGKONG TERFERMENTASI) SEBAGAI PAKAN TERNAK MENJADI BERAS ANALOG - Astari Ratnaduhita; Dimas Fajar Nugroho; Desna Ayu Wijayanti (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2023)
This research's aim is to analyze the potential of gathot in analog rice with CMC and red bean flour, according to physicochemical quality and hedonic test. This study consisted of 4 treatments and 5 times repetition. The treatment was the addition of CMC with a level of 0; 1; 2; 3% in analog rice. The test includes water absorption, crude fiber content and aftertaste with hedonic test. Analyzing data by Completely Randomized Design (RAL) and processed using SPSS 23.0. The results is gathot's analog rice with CMC and red bean flour influences the water absorption and crude fiber content. The best performance of CMC 1% in gathot's analog rice with the water absorption of 161,28% and crude fiber content of 4,98%.